Mutagenesis - Mishra, Rajnikant (IntechOpen, 2012)
The complexity of problem understanding biochemical and molecular basis of healthy life, and eagerness to find simple solution necessitate evolution of technology like mutagenesis. The chapters of this book contain experiences of scientists working in the area of mutagenesis. It describes suitable experimental models (microorganism, plants or animals) for testing spontaneous and induced mutations which are useful for basic and translational research. It includes methods towards gene targeting, developing disease and pest resistant plants, creating temperature sensitive molecular machines, understanding mitochondrial mutagenesis, detecting anti-mutagens, improving genetic insight into impaired immunity and disease. It also describes mutagenesis induced by DNA damage. It has also provided advantage of in vitro transcription and translation to yield proteins with point mutations, deletions or insertions for studying stability, DNA-protein or protein-protein interaction. Trust, it will serve readers as valuable integrated resources emphasizing methods of mutagenesis, and understanding mechanism of variable penetrance or expressivity of mutations.